A Method for the Determination of Composition Profiles in Industrial Air Separation, Pressure Swing Adsorption Systems - C.C.K. Beh; P.A. Webley (Adsorption Science & Technology)
A simplified energy-balance equation has been proposed as an aid to online measurement of the adsorbed-phase nitrogen loading in industrial-scale pressure and vacuum swing adsorption systems consisting of one preferentially adsorbed component. Implementation of this technique to current and future plants requires the addition of thermocouples (which are relatively inexpensive) located axially through the bed and pressure transmitters at the bottom and top of the bed. This methodology has the advantage that the composition front may be inferred accurately from direct measurements of the local pressure and temperature, and used as the basis for process monitoring and diagnostics of plant purity, recovery and production rate.